The Effect of Teaching Techniques and Learning Styles to Improve Students’ Speaking Skill - Yulyani, Rani Dewi (Department of Indonesian Language Education, Graduate School, University of Muhammadiyah Prof. DR. HAMKA, 2018)
This research aims, firstly, to analyze the significant effect of role-play and discussion techniques on the students? speaking skill. Secondly, to analyze the significant difference of the students who are holistic learners with those who are sequential learners regarding their speaking skill. Thirdly, to discuss the interaction regarding the teaching techniques and learning style concerning the students? speaking skill. The objects of the research were two classes of English department students, Universitas Pamulang (UNPAM). The instruments used were the speaking test and questionnaires. The method of the data analysis was quantitative using SPSS 20. The result of the research shows, firstly, there was a significant effect of the role-play technique and discussion on the students? speaking skill. Secondly, there was no significant difference concerning the students who are holistic learners with those who are sequential learners, regarding the speaking skill. Thirdly, there was no interaction between teaching techniques and learning styles in relation with students? speaking skill.